Ce (III)-terephthalic acid metal-organic frameworks as highly efficient ·OH radical scavengers for fuel cells and investigation of its antioxidation mechanism. (January 2023) - Xu, Kangwei; Pei, Supeng; Zhang, Wei; Han, Zhiyue; Guan, Panpan; Wang, Li; Zou, Yecheng; Ding, Han; Ma, Xiaojuan; Xu, Caidi; Liu, Feng; Zhang, Yongming
Abstract: Herein, in order to relieve the chemical degradation of perfluorosulfonic acid (PFSA) membranes without decreasing their proton conductivity, Ce (III)-terephthalic acid metal-organic frameworks (Ce-TPA MOFs) with efficient ·OH radical scavenging efficiency are designed via coordinating the organic antioxidant ligand (TPA) with inorganic radical scavenger (Ce ions). Ce-TPA MOFs with a different weight ratio of 0.5, 1.0, or 2.0% was introduced in PFSA matrix to produce composite membranes. On the one hand, the hydrophilic groups of Ce-TPA MOFs caused better water absorption, which promoted the proton conduction to some extent. Also, the presence of the redox Ce 3+ /Ce 4+ couple, oxygen vacancy, and TPA molecules in Ce-TPA MOFs scavenging ·OH radical together via synergy effect. The optimum peak power density of the PFSA/Ce-TPA1.0 composite membrane at 75 °C under 80% relative humidity was 1086 mW/cm that of pristine PFSA membrane was only 1032 mW/cm. Furthermore, PFSA/Ce-TPA1.0 composite membrane experienced the decay of only 0.31 mV/h during 96 h operation under the same conditions, whereas that of pristine PFSA membrane was 2.20 mV/h. Thus, the PFSA/Ce-TPA membrane was a potential candidate for proton exchange membrane fuel cells. Graphical abstract: Image 1 Highlights: Improve chemical durability of the proton exchange membrane by doping with Ce (Ⅲ)-terephthalic acid metal-organic frameworks (Ce-TPA MOFs). Ce-TPA MOFs can eliminate ·OH radical by the synergy effect of terephthalic acid and redox Ce 3+ /Ce 4+ couple. Introduction of Ce-TPA MOFs to proton exchange membrane led to improved power density. Optimized composite membrane (0.31 mV/h) showed much lower open-circuit voltage degradation than pristine perfluorosulfonic acid (2.20 mV/h).